The Digital-Green Twin Transition: A Framework for Digital Transformation and Clean Energy Integration in the Agro-Industrial Sectors of Russia and Kazakhstan - Rustenova, Elvira; Ibyzhanova, Aizhan; Aidaraliyeva, Aizhamal; Barykin, Sergey; Voronova, Olga; Penkova, Inessa Vyacheslavovna; Daniali, Sara (International Journal of Energy Economics and Policy, 2026)
This study examines the relationship between Digital Transformation (DT) and Clean Energy Integration (CEI) in the agro-industrial sectors of emerging economies, with a focus on Kazakhstan and Russia. As these countries pursue industrial growth while meeting climate commitments, the research evaluates how digital maturity and green financial frameworks drive decarbonization. Using secondary data from 2000 to 2024, the study applies advanced econometric methods, including Cross-Sectionally Augmented IPS (CIPS) unit root tests and the Cross-Sectionally Augmented Autoregressive Distributed Lag (CS-ARDL) model, to address cross-sectional dependence and structural breaks. Results show that both Digital Transformation and Environmental Policy (EP) significantly reduce Greenhouse Gas Emissions (GHGE) in the long term, with coefficients of −1.730 and −2.289, respectively. Green Financial Innovation (GFI) and Circular Capacity (CC) also play key roles in lowering carbon intensity. The Error Correction Term (ECT) of −1.120 suggests a rapid adjustment toward the long-run equilibrium. This research introduces a holistic “Digital-Green Twin” approach, positioning digitalization as the foundation for renewable energy adoption in large-scale agro-industrial processing. The findings offer a scalable roadmap for policymakers to align technological progress with carbon-neutral industrial objectives.